Factorial exploration of organizational climate and culture within the framework of the competing values model - Hernández Sampieri, Roberto (2012)
The purpose of this study was to continue the exploration of a model in the mexican labor field that contextualizes organizational climate and links it with organizational culture. This research was based in the study of privanza Hernández Sampieri (2008) who choose the Competing Values Framework (CVF) with the same objective. Overall, the findings of the study founded the model in a heterogeneous sample of 11 organizations (n=973) in the central region of Mexico. In addition to the model, we tried to improve the instrument designed by Hernández Sampieri (2008) which intent to measure organizational climate according to the CVF. The instrument proved in general, with reliability and validity, the capability to discriminate amongst organizations.